2022
DOI: 10.1155/2022/4805300
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Value and Imaging Features of Bedside High‐Frequency Ultrasound Imaging in the Diagnosis of Neonatal Pneumonia

Abstract: The aim is to solve the problem of the urgent need of a nonradiation, noninvasive, and simple-to-operate diagnostic method for neonatal pneumonia that can indicate the severity of the disease and dynamically monitor the outcome of the disease. The authors propose a bedside high-frequency ultrasound technique based on methods for evaluation in the detection and treatment of neonatal pneumonia. The results obtained are as follows: the sensitivity of neonatal lung ultrasound in the diagnosis of neonatal pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The lung high frequency ultrasonography score reduced by 35% after three days of treatment and by 68% after seven days of treatment, showing that it is very successful at describing the state of the treatment. It has been shown that pneumonia in new-born can be diagnosed efficiently using lung ultrasonography (17).…”
Section: Clinical Applications and Significance; Reflection From Lite...mentioning
confidence: 99%
“…The lung high frequency ultrasonography score reduced by 35% after three days of treatment and by 68% after seven days of treatment, showing that it is very successful at describing the state of the treatment. It has been shown that pneumonia in new-born can be diagnosed efficiently using lung ultrasonography (17).…”
Section: Clinical Applications and Significance; Reflection From Lite...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%